Correction: A Randomized, Double-Blind, Positive-Controlled, Multicenter Clinical Trial on the Efficacy and Safety of ShuganJieyu Capsule and St. John's Wort for Major Depressive Disorder with Somatic Complaints. - Xiang, Yajie; Wang, Lihua; Gu, Ping; Wang, Chunxue; Tian, Yuling; Shi, Wanying; Deng, Fang; Zhang, Yongbo; Gao, Li; Wang, Kai; Wang, Yi; He, Jincai; et al. (International Journal of Mental Health & Addiction, 2025)
The article focuses on the correction of errors in a previous study regarding the baseline demographic and clinical characteristics of participants in a clinical trial comparing ShuganJieyu Capsule and St. John's Wort. It highlights the correction of the term "pre-protocol" to "per-protocol" in the statistical analysis section and addresses typographical errors in Table 1 related to co-prescriptions and various health assessments. The corrected data includes demographic details such as age, gender, body mass index (BMI), and various health scales, ensuring the integrity of the study's findings remains intact.